NILAI RUJUKAN HEMATOLOGI ORANG DEWASA NORMAL DI RSUD ULIN BANJARMASIN - Azma Rosida; FX Hendriyono (Berkala Kedokteran, 2015)
Results of laboratory tests are interpreted through value. Hematological examination is an examination that is often requested and performed to determine the state of the blood and its components so that the patient's medical condition can be known. Reference value can be obtained from brochure instruments or laboratory has its own research using populations in the laboratory because of possible variation between the laboratory values with other laboratories due to differences in methods of examination and patient characteristics. The objective of the study is to get hematology reference values in Ulin Hospital, Banjarmasin. This study is cross-sectional observasional analytic  study, conducted in hospitals Ulin Banjarmasin, June-July 2014. The subject of the study consisted of 120 women and 120 men who came for medical examinations in clinical pathology laboratories Hospital Ulin, Banjarmasin. Results obtained Hb 12.5-16.7 from the men and women are from 12.0 to 15.6 g / dL. The numbers of male erythrocytes are from 4.1 to 6.0 million / uL and women are 4.0 to 5.3 million / uL. Leukocyte numbers are 4650-10300 / uL. Platelet numbers are 150-356 thousand from men and women are 177-401 thousand / uL. Parameters 75-96 fL MCV, MCH 28-32 pg, MCHC 33-37 g / dL, and RDW-CV 12.1 to 14%. The results of this study did not differ significantly with the reference value that has been used but the obtained values of MCV are lower. Keywords: Reference value, haematology, normal adult,  RSUD Ulin